2017
DOI: 10.1007/s11901-017-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

Why Doesn’t Primary Biliary Cholangitis Respond to Immunosuppressive Medications?

Abstract: Purpose of ReviewThe purpose of this review is to discuss reasons why immunosuppressive therapy so far failed in Primary Biliry Cholangitis.Recent FindingsEven targeted immunosuppressive therapy seems ineffective or potentially harmful.SummaryBile acid-mediated cholangiocyte damage, facilitated by insufficient bicarbonate secretion, seems to attenuate the anti-inflammatory and anti-fibrotic actions of immunosuppressant and immunomodulatory drugs in a clinically significant way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…45 In a context of reduced liver AE2 expression and AE2 deficiency, there may occur defective bicarbonate umbrella and subsequent entry of protonated bile salts into cholangiocytes (concisely and nicely reviewed in ref. 12 ). Entry of highly hydrophobic bile salts can promote reactive oxygen species (ROS) production, and lead to enhanced inflammatory cytokine and chemokine responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 In a context of reduced liver AE2 expression and AE2 deficiency, there may occur defective bicarbonate umbrella and subsequent entry of protonated bile salts into cholangiocytes (concisely and nicely reviewed in ref. 12 ). Entry of highly hydrophobic bile salts can promote reactive oxygen species (ROS) production, and lead to enhanced inflammatory cytokine and chemokine responses.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these features of autoimmunity in PBC, the therapeutic regimes with potent immunosuppressants have shown little efficacy, which is particularly intriguing if compared with the substantial benefit obtained in most patients with early PBC undergoing therapy with ursodeoxycholic acid (UDCA). [12][13][14][15][16] Since the hydrophilic bile acid UDCA is known to induce bicarbonate-rich choleresis, we have been postulating that primary or secondary abnormalities in the mechanisms responsible for biliary bicarbonate secretion might have a pathogenic role in PBC. [17][18][19][20][21] Indeed, positron-emission-tomography studies showed that untreated patients with PBC failed to increase biliary bicarbonate in response to secretin, while treatment with UDCA for a few months could reverse this defect.…”
Section: Introductionmentioning
confidence: 99%
“…Patients without AMA can develop PBC, whereas a proportion of patients with AMA do not [10]. Furthermore, immunosuppression has proven to be of little utility for PBC patients, whereas bile modulation therapy with ursodeoxycholic acid and more recently with the potent FXR receptor agonist obeticholic acid, have become the standard of care [11]. Nevertheless, the common perception remains that PBC patients have autoimmune destruction of bile ducts [8] but this assumption is prevalent (and rarely challenged) even though pertinent validation is lacking.…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%
“…ACA recognize six centromere polypeptides belonging to the kinetochore proteins: Therapy PBC treatment is currently based on UDCA, which is the only approved drug. Its mechanism of action is incompletely understood and possibly dependent on the various phases of the disease 5,92 .…”
Section: Association With Rheumatic Diseasesmentioning
confidence: 99%